1980
DOI: 10.1001/jama.1980.03300310031018
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Mortality and Causes of Death in Morbidly Obese Men

Abstract: A group of 200 morbidly obese men (average weight, 143.5 kg; age, 23 to 70 years) were admitted to a weight control program between 1960 and 1977 and were followed up for a mean period of 7 1/2 years. There was complete follow-up until the termination of the study or until death for 185 men. Fifteen men were followed up for fractional periods. Fifty of the 200 died during the course of the study. Life-table techniques, comparing the mortality among the obese with that among men in the general population, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
18

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(70 citation statements)
references
References 6 publications
0
52
0
18
Order By: Relevance
“…There is a direct association between obesity and several diseases like diabetes mellitus, hypertension, dyslipidaemia and ischemic heart disease 25. Weight gain appears to precede the development of diabetes 26.…”
Section: Discussionmentioning
confidence: 99%
“…There is a direct association between obesity and several diseases like diabetes mellitus, hypertension, dyslipidaemia and ischemic heart disease 25. Weight gain appears to precede the development of diabetes 26.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with an increased risk of coronary artery disease (CAD) and mortality [6-8]. Morbidity and mortality rates rise proportionally to the degree of obesity in men and women and the impact of excess body fat is more significant in younger subjects than older ones [9-12].…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients cardiomyopathies are manifested as longer P-wave, and increased QT c dispersion (Seyfeli et al, 2006; Nielsen et al, 2013b). Since altered QT c is also associated with sudden cardiac death (SCD), Drenick et al found that in obesity SCD is 12-fold higher in patients aged 25–34, and 6-fold higher in in age group 35–44 years (Drenick et al, 1980). On the other hand, Kannel et al found that there was no association between obesity and SCD (Kannel et al, 1998).…”
Section: Ionic Mechanisms Of Cardiomyopathies Of Obesitymentioning
confidence: 99%